The Impact of COVID-19 Pandemic on Malaysian Stock Performance - Wei Jie, Lee; Venus Khim Sen, Liew; Shirly Siew Ling, Wong (HRMARS, 2025)
The COVID-19 pandemic occurs in year 2020 bring huge impact in worldwide. The global stock market was affected by the COVID-19 pandemic including Malaysia’s stock market. The purpose of this study is to determine the impact of the COVID-19 pandemic on Malaysian stock performance. This study will employ the Kendall’s tau-b correlation analysis to determine the impact of the COVID-19 pandemic. The data collected are daily data from 25th January 2025 to 31st December 2025. The dependent variable is the Kuala Lumpur Composite Index (KLCI) while the independent variables are built up from two categories which are the COVID-19 variables and the control variables. The COVID-19 variables include the confirmed cases, death cases and recovery cases. On the other hand, the control variables include the oil price, gold price, exchange rate, volatility index and NASDAQ composite index. The result showed the COVID-19 variables had significant impact on KLCI.